2016
DOI: 10.1371/journal.pone.0162851
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis of Wheat Seeds during Artificial Ageing and Priming Using the Isobaric Tandem Mass Tag Labeling

Abstract: Wheat (Triticum aestivum L.) is an important crop worldwide. The physiological deterioration of seeds during storage and seed priming is closely associated with germination, and thus contributes to plant growth and subsequent grain yields. In this study, wheat seeds during different stages of artificial ageing (45°C; 50% relative humidity; 98%, 50%, 20%, and 1% Germination rates) and priming (hydro-priming treatment) were subjected to proteomics analysis through a proteomic approach based on the isobaric tande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 111 publications
11
49
0
Order By: Relevance
“…One of the most important factors in the production of wheat is the quality of the seeds that have been planted. The quality of wheat seeds is affected by many factors, including cultivar, genetic purity, physical purity, vitality, germination percentage, and seed viability (Lv et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important factors in the production of wheat is the quality of the seeds that have been planted. The quality of wheat seeds is affected by many factors, including cultivar, genetic purity, physical purity, vitality, germination percentage, and seed viability (Lv et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Protein disulfide isomerases (PDIs) are enzymes found primarily in the endoplasmic reticulum (ER) in eukaryotes play a vital role in protein folding. The up-regulated levels of PDIs (A0A024FRN3, A0A1D5XQP7, A0A1D5XQP9, B9A8E3, F8THZ6, Q6JAB5, Q93XQ8) in the present study indicated the higher PDI activity (MF) and confirmed the active status of protein synthesis (Hayano et al ., 1995; Lv et al ., 2016; Kayum et al ., 2017) and higher resistance to abiotic stresses (Kayum et al ., 2017). This conclusion was strongly confirmed by the upregulation of 60S ribosomal protein L29 (A0A1D5RRD3), 40S ribosomal protein S12 (A0A1D5UFM0, A0A1D5UVS7) and Eukaryotic translation initiation factor 4B1 (Q9AUJ7) (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, acetyl-CoA carboxylase activity is found in the plastids and catalyzes the first committed step of de novo fatty acid biosynthesis by the carboxylation of acetyl-CoA to malonyl-CoA (Fazli et al ., 2005; Liu et al ., 2007; Lv et al ., 2016). In the present study, acetyl-CoA carboxylase (Q8L4W1), plastid acetyl-CoA carboxylase (fragment) (A0A068B0K3, A0A068B0L8, A0A068B0M7, A0A068B226, A0A068B2H1, A0A068B2I1, A0A068B3I5, A0A068B675, B1A0F0, D0V7D7, D0V7D9, D0V7E1, D0V7E3, D0V7F1) and acetyl-coenzyme A carboxylase (Fragment) (O48960), were down-regulated, indicating that CoA carboxylase activity (GO:0016421), acetyl-CoA carboxylase activity (GO:0003989) and biotin carboxylase activity (GO:0004075) were affected.…”
Section: Discussionmentioning
confidence: 99%
“…The original germination rate (Gr) was 97.0% (designated as YM97), and the average seed moisture content was 12.19%. A 400 g sample of seeds with a similar size and weight was stored in a 5 L plastic bottle at 45 ± 1°C and 50% relative humidity in a constant temperature-and humidity-controlled cabinet (Binder KMF720, Tuttingen, Germany) according to our previous research (Lv et al, 2016). Measurement of CO 2 from wheat respiration and calculation of Gr were performed as previously described (Dong et al, 2015;Zhang et al, 2014).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%
“…2.3. Liquid chromatography tandem mass spectrometry (LC-MS/MS) analysis and database searches LC-MS/MS and database searches were performed as described previously (Lv et al, 2016).…”
Section: Protein Extraction Sds-page Analysis Trypsin Digestion Tmmentioning
confidence: 99%